Respostas
respondido por:
14
Teria como me dar 12 pontos??
Seria isso??
( t -1)² + (t+ 2)² - 9 =0
(t - 1).(t - 1) + (t + 2).(t + 2) - 9 = 0
t²- t - t + 1 + (t² + 2t + 2t + 4) - 9 = 0
t² - 2t + 1 + (t² + 4t + 4) - 9 = 0
t² - 2t + 1 + t² + 4t + 4 - 9 = 0
t² + t² - 2t + 4t + 1 +4 - 9 = 0
2t² + 2t + 5 - 9 = 0
2t² + 2t - 4 = 0 ÷ (2)
t² + t - 2 = 0
a = 1 b = + 1 c = - 2
Δ = b² -4.a.c
Δ = (1)² - 4.(1).(-2)
Δ = 1 + 8
Δ = 9
t = - b ± √Δ
2.a
t = - (+1) ± √9
2.1
t = - 1 ± 3
2
t'= - 1 + 3 = 2 = 1
2 2
t"= - 1 - 3 = - 4 = - 2
2 2
Seria isso??
( t -1)² + (t+ 2)² - 9 =0
(t - 1).(t - 1) + (t + 2).(t + 2) - 9 = 0
t²- t - t + 1 + (t² + 2t + 2t + 4) - 9 = 0
t² - 2t + 1 + (t² + 4t + 4) - 9 = 0
t² - 2t + 1 + t² + 4t + 4 - 9 = 0
t² + t² - 2t + 4t + 1 +4 - 9 = 0
2t² + 2t + 5 - 9 = 0
2t² + 2t - 4 = 0 ÷ (2)
t² + t - 2 = 0
a = 1 b = + 1 c = - 2
Δ = b² -4.a.c
Δ = (1)² - 4.(1).(-2)
Δ = 1 + 8
Δ = 9
t = - b ± √Δ
2.a
t = - (+1) ± √9
2.1
t = - 1 ± 3
2
t'= - 1 + 3 = 2 = 1
2 2
t"= - 1 - 3 = - 4 = - 2
2 2
Perguntas similares
7 anos atrás
7 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás